2020
DOI: 10.1007/s00134-020-06028-z
|View full text |Cite
|
Sign up to set email alerts
|

Correction to: Clinical predictors of mortality due to COVID-19 based on an analysis of data of 150 patients from Wuhan, China

Abstract: Springer Nature remains neutral with regard to jurisdictional claims in published maps and institutional affiliations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
312
0
17

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 400 publications
(346 citation statements)
references
References 0 publications
13
312
0
17
Order By: Relevance
“…Leucine-Rich Alpha-2-Glycoprotein LRG1 expression is induced by IL-6 (Shirai et al, 2009) , which is elevated in severe COVID-19 (Ruan et al, 2020) . LRG1 promotes angiogenesis (Wang et al, 2013) and has been reported to be associated with local inflammation (Naka and Fujimoto, 2018) .…”
Section: Supplementary Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Leucine-Rich Alpha-2-Glycoprotein LRG1 expression is induced by IL-6 (Shirai et al, 2009) , which is elevated in severe COVID-19 (Ruan et al, 2020) . LRG1 promotes angiogenesis (Wang et al, 2013) and has been reported to be associated with local inflammation (Naka and Fujimoto, 2018) .…”
Section: Supplementary Informationmentioning
confidence: 99%
“…Elevated in acute-phase response (Jain et al, 2011) . Of note, HP expression is known to be promoted by IL-6 , which is elevated in severe COVID-19 (Ruan et al, 2020) .…”
Section: Supplementary Informationmentioning
confidence: 99%
“…Elderly people and people who have underlying medical conditions are at higher risk for developing more serious complications, such as septic shock, ARDS, acute kidney injury (AKI), and fulminant myocarditis. 6,7 Approximately 81% of deaths occurred among people aged >60 years in China. 5 As a new infectious disease, COVID-19 is characterized by severe acute respiratory injury and hyperinflammation-related syndromes.…”
Section: Introductionmentioning
confidence: 99%
“…Although most cases are mild to moderate in severity, about 15% develop severe pneumonia, and nearly 5% progress to acute respiratory distress syndrome and multiple organ failure [25,49]. This worsening is predominantly driven by cytokine upregulation and an exaggerated yet maladaptive inflammatory response [35,40,47]. Direct viral infection and cytopathic effects may also play a role.…”
Section: Introductionmentioning
confidence: 99%